Quantifying outcomes for leech therapy in digit revascularization and replantation. (May 2019) - Lee, Z-Hye; Cohen, Joshua M.; Daar, David; Anzai, Lavinia; Hacquebord, Jacques; Thanik, Vishal
We retrospectively reviewed 201 digit replantations or revascularizations that were performed between August 2007 and June 2015. Leeching therapy was used in 48 digits and was more commonly required in replanted digits. In revascularized digits, leeching was used significantly more frequently in avulsion injuries and injuries associated with fractures. Digits that were leeched for more than 4.5 days had significantly higher rates of survival of digits after replantation or revascularization. Leeching was associated with higher incidence of transfusion, higher mean number of transfusions, and longer length of stay. We conclude from this study that leeching is used more frequently after digital replantation than revascularizaion, and in revascularized digits, leeching is used more often in avulsion injury and in patients with fractures. In patients requiring leeching therapy, leaching for more than 4.5 days leads to higher rate of digital survival. Level of evidence: IV